To transform an expression in polar form to Cartesian (or rectangular) form, we need the formulas that relate r and theta to x and y.
Step 1. Recall the relationships between polar and Cartesian.
x^2+y^2=r^2
x=rcos(theta) or cos(theta)=x/r or theta=cos^-1(x/r)
y=rsin(theta) or sin(theta)=y/r or theta=sin^-1(y/r)
tan(theta)=y/x
These relationships can be determined from drawing a point in one of two ways, as radius and angle or as x-coordinate and y-coordinate as seen below.
Step 2. Convert each term from polar to Cartesian.
We are given r-5theta=sin^3(theta)+sec(theta). Let's take each part and put it terms of x and y.
r=sqrt(x^2+y^2)
5theta=5sin^-1(y/r)
Plugging r=sqrt(x^2+y^2) into the previous gives
5theta=5sin^-1(y/sqrt(x^2+y^2))
sin^3(theta)=(y/r)^3=(y/sqrt(x^2+y^2))^3
sec(theta)=1/cos(theta)=r/x=sqrt(x^2+y^2)/x
Step 3. Plug these back into the original.
r-5theta=sin^3(theta)+sec(theta) becomes
sqrt(x^2+y^2)-5sin^-1(y/sqrt(x^2+y^2))=(y/sqrt(x^2+y^2))^3+sqrt(x^2+y^2)/x
You could spend a lot of time trying to simplify and trying to find a function y in terms of the independent variable x, but this is not what your question asked. So this is a great place to stop!